Macrophage and T-Cell Infiltration and Topographic Immune Cell Distribution in Non-Melanoma Skin Cancer of the Head and Neck - Frohwitter, Gesche; Kerta, Marie; Vogl, Christoph; Geppert, Carol Immanuel; Werry, Jan-Erik; Ries, Jutta; Kesting, Marco; Weber, Manuel (Frontiers in Oncology, 2022)
Non-melanoma skin cancer (NMSC) is a heterogenous tumor entity that is vastly determined by age and UV-light exposure leading to a great mutational burden in cancer cells. However, the success of immune checkpoint-blockade in advanced NMSC as well as the incidence and disease control rates of NMSC in organ transplant recipients compared to immunologically uncompromised patients point towards the emerging importance of the immunologic activity of NMSC. To gain first insight into the role of T cell and macrophage infiltration in NMSC of the head and neck and capture their different immunogenic profile, which appears to be highly relevant for the response to immunotherapy, we conducted a whole slide analysis of 107 basal cell carcinoma (BCC) samples and 117 cutaneous squamous cell carcinoma (cSCC) samples. The CD8+ and CD68+ immune cell expression in both cancer types was evaluated by immunohistochemistry and a topographic distribution profile as well as the proportion of both cell populations within the two tumor entities was assessed. The results show highly significant differences in terms of CD8+ T-cell and CD68+ macrophage infiltration in BCC and cSCC and indicate cSCC a highly immunogenic tumor. Yet BCC presents with less immune cell infiltration, the relation between the immune cells compared to cSCC does not show any significant difference. These findings help to explain the disparities in local aggressiveness, distant metastasis as well as the eligibility for immune checkpoint blockade in both tumor entities and encourage further research.